Investigation of the physical-mechanical properties of timber using ultrasound examination - Teder, Marko; Pilt, Kalle; Miljan, Matis; Pallav, Vello; Miljan, Jaan (Journal of Civil Engineering and Management, 2012)
This research uses a non-destructive method – ultrasound – to examine timber, combining the results of measurement with the properties of strength and stiffness. The purpose of this work is to explore the possibilities of grading wood structure in situ using ultrasound measurements, specifically, the moisture content and density of the timber. The timber used in these experiments was taken from existing buildings of different ages. The potential of replacing direct measurements with indirect measurements by ultrasound was also investigated. The physical-mechanical properties of wood were determined in laboratory conditions according to standard practices, and the method of non-destructive measurements was based on a commercial test device based on 54 kHz compressional wave 50 mm diameter ultrasound transducers. Direct measurements were performed in the longitudinal and radial material directions. Indirect measurements were performed with transducers positioned on the same lateral surface of the sample. A weak correlation was found with-in the different measurements. Longitudinal measurements characterise bending strength with R2 = 0.18 and modulus of elasticity with R2 = 0.37. In multiple regression analysis, stronger correlations were found; prediction equations of bending strength and modulus of elasticity were found with R2 = 0.40 and R2 = 0.81, respectively.